EGR1 as a potential marker of prognosis in extranodal NK/T-cell lymphoma - Ji Yun Lee; Joo Hyun Kim; Heejin Bang; Junhun Cho; Young Hyeh Ko; Seok Jin Kim; Won Seog Kim (Scientific Reports, 2021)
Abstract Extranodal natural killer T-cell lymphoma (ENKTL) is an aggressive malignancy with a dismal prognosis. In the present study, gene expression profiling was performed to provide more information on ENKTL molecular signature and offer a rationale for further investigation of prognostic markers in ENKTL. NanoString nCounter Analysis encompassing 133 target genes was used to compare gene expression levels of 43 ENKTL tumor samples. The majority of the patients were under 60 years of age (79.1%); 32 (74.4%) patients had nasal type ENKTL and 23 patients (53.5%) had intermediate/high risk ENKTL based on the prognostic index for natural killer cell lymphoma (PINK). The median follow-up was 15.9 months and the median overall survival (OS) was 16.1 months (95% CI 13.0–69.8). EGR1 upregulation was consistently identified in the localized stage with a low risk of prognostic index based on the PINK. Among the six significantly relevant genes for EGR1 expression, high expression levels of genes, including CD59, GAS1, CXCR7, and RAMP3, were associated with a good survival prognosis. The in vitro test showed EGR1 modulated the transcriptional activity of the target genes including CD59, GAS1, CXCR7, and RAMP3. Downregulation of EGR1 and its target genes significantly inhibited apoptosis and decreased chemosensitivity and attenuated radiation-induced apoptosis. The findings showed EGR1 may be a candidate for prognostic markers in ENKTL. Considerable additional characterization may be necessary to fully understand EGR1.